"THE CONCEPT OF NATIONAL EDUCATION AND ITS PEDAGOGICAL SIGNIFICANCE" (Universal International Scientific Journal, 2026)
This article reveals the essence of the concept of national education, its role and significance in the pedagogical process. The spiritual issues of national consciousness in young people receiving education through national education are analyzed. At the same time, the systematicity and significance of national education in the educational process are analyzed based on scientific sources.
Keywords: National education, pedagogical process, spiritual and educational education, patriotism, national identity, national consciousness, social education, harmony of education and upbringing, national value, harmonious generation